Induction of Apoptosis in Human Cancer Cells by Human Eb- or Rainbow Trout Ea4-Peptide of Pro-Insulin-Like Growth Factor-I (Pro-IGF-I) - Chen, Maria J.; Lin, Chun-Mean; Chen, Thomas T. (IntechOpen, 2012)
None